1991
DOI: 10.1097/00005072-199101000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Modulation of HLA-DR on Cultured Human Adult Astrocytes

Abstract: Expression of Class II major histocompatibility complex (MHC) antigens on astrocytes has been implicated as contributing to the immune responses characteristic of chronic autoimmune diseases of the central nervous system. We examined the properties and regulation of HLA-DR on cultured human adult astrocytes. We found that a proportion of human astrocytes from each of fifteen individual donors expressed HLA-DR under basal culture condition; while this proportion differed among the human subjects (range 3-65%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…As shown in Table 11, IFN-y increased the proportion of astrocytes expressing HLA-DR, as we have previously documented (Yong et al, 1990). In this regard, both the process-bearing and flat astrocytes could be induced to express HLA-DR to similar levels.…”
Section: Resultssupporting
confidence: 79%
“…As shown in Table 11, IFN-y increased the proportion of astrocytes expressing HLA-DR, as we have previously documented (Yong et al, 1990). In this regard, both the process-bearing and flat astrocytes could be induced to express HLA-DR to similar levels.…”
Section: Resultssupporting
confidence: 79%
“…We then used ingenuity pathway analysis (IPA) to query pathways associated with the resulting genes and identified the antigen presentation pathway as the most significantly represented pathway increased in TAAs relative to normal astrocytes (Table 1). While previously published data has shown astrocytes to have antigen-presenting capabilities in vitro as well as in in vivo injury models [31][35], this function of stromal astrocytes has not been identified in a glioma mouse model. We used immunoflourescent staining to confirm MHC class II expression on TAAs in low-grade gliomas and GBM (Figure S3A) and stained with Iba-1, an immune cell marker, to demonstrate that these MHC class II-expressing astrocytes were not microglia or macrophages.…”
Section: Resultsmentioning
confidence: 85%
“…These molecules are important for antigen presentation to T cells. While previously published data has shown that astrocytes possess antigen-presenting capabilities ex vivo and in models of brain injury [31][35], this function of astrocytes has not been identified in a glioma mouse model and highlights a novel and potentially important role for TAAs.…”
Section: Discussionmentioning
confidence: 88%
“…The induction of class I1 MHC antigens on astrocytes by a variety of factors, including interferon (1FN)-gamma, tumor necrosis factor (TNF)-enhanced IFN-induced responses, and certain viruse~,2.54,58.59. 142,222,259,273 suggests that astrocytes may be involved in immune-mediated disease. In experimental allergic encephalomyelitis (EAE), astrocytes and other cells, including microglia and endothelium, express MHC class I1 mo1ecules.54~5y~155~156 Cells that express class I1 antigens are also present in active lesions of multiple sclerosis (MS), and at least some of these appear to be astrocytes.132 There is controversy, however, concerning which cells indigenous to the CNS, astrocytes or microglia, actually serve as antigen-presenting cells in these diseases.…”
Section: Astrocytes In Demyelinating Diseasementioning
confidence: 99%